Pollen collected by stingless bees Tetragonula laeviceps (Smith, 1857) (Hymenoptera: Apidae: Meliponini) from Central Sulawesi - Masrianih Masrianih; Fatmah Dhafir; Manap Trianto (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2022)
The diversity of pollinating insects is used as conservation management. Pollen is gametophyte from male which can give characteristics to its offspring. The pollen carried by bees can be used as an identification of feed favored by bees. This study aims to identity pollen derived from the legs of stingless bees based on the color morphological characteristics of the pollen. The methods include color identification of pollen collected by stingless bees, pollen extraction, acetolysis, and pollen identification. Pollen with the same species at the study site has a color that is not much different. Stingless bees take pollen based on the size and distance of the plant to the hive. Smell and color as a secondary binder for stingless bees. Different plant pollen species can also be influenced by the protein requirements of each stingless bee colony. It can recognize the presence of flowering plants aroud the hive. The size of pollen can affect the bees in taking plant pollen.